Pengaruh Pengendalian Internal, Asimetri Informasi Dan Moralitas Individu Terhadap Kecenderungan Kecurangan Akuntansi Pada Dinas Pemberdayaan Masyarakat Dan Desa Kabupaten Pulang Pisau - Intan junita; Fitria Husnatarina; M. Ichsan Diarsyad (Jurnal Riset dan Inovasi Manajemen, 2023)
This study aims to examine the effect of Internal Control, Information Asymmetry and Individual Morality on the Tendency of Accounting Fraud in the Community and Village Empowerment Services of Pulang Pisau Regency. The method used in this study is a quantitative research method by distributing questionnaires. The sample in this study was selected using the saturated sampling method and a sample of 30 respondents was obtained. The data analysis method used is multiple linear regression analysis. Testing is done partially and simultaneously. The results of this study indicate that partially Internal Control and Information Asymmetry have no effect on the Tendency of Accounting Fraud. Meanwhile, individual morality influences the tendency of accounting fraud. The coefficient of determination (adjusted R square) is 0.104 or 10.4%. This means that 10.4% of the variable Accounting Fraud Tendencies can be explained by the variables Internal Control, Information Asymmetry and Individual Morality. While the remaining 89.6% (100%-10.4%) can be explained by other variables outside the research